2007
DOI: 10.1088/1741-2560/4/3/018
|View full text |Cite
|
Sign up to set email alerts
|

Free-paced high-performance brain–computer interfaces

Abstract: Neural prostheses aim to improve the quality of life of severely disabled patients by translating neural activity into control signals for guiding prosthetic devices or computer cursors. We recently demonstrated that plan activity from premotor cortex, which specifies the endpoint of the upcoming arm movement, can be used to swiftly and accurately guide computer cursors to the desired target locations. However, these systems currently require additional, non-neural information to specify when plan activity is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(48 citation statements)
references
References 27 publications
2
46
0
Order By: Relevance
“…These numbers lie within the previously reported range of ϳ10 -20 neurons (Serruya et al, 2002;Taylor et al, 2002), and several tens to hundreds of neurons (Wessberg et al, 2000;Carmena et al, 2003;Musallam et al, 2004). In addition, we could show that it is feasible to jointly decode direction and task time albeit at a significant cost in performance for direction decoding [complementing the results of Achtman et al (2007)]. Both results could be of practical relevance for future BMI applications in patients (Hochberg et al, 2006).…”
Section: Relevance For Brain-machine Interfacessupporting
confidence: 87%
“…These numbers lie within the previously reported range of ϳ10 -20 neurons (Serruya et al, 2002;Taylor et al, 2002), and several tens to hundreds of neurons (Wessberg et al, 2000;Carmena et al, 2003;Musallam et al, 2004). In addition, we could show that it is feasible to jointly decode direction and task time albeit at a significant cost in performance for direction decoding [complementing the results of Achtman et al (2007)]. Both results could be of practical relevance for future BMI applications in patients (Hochberg et al, 2006).…”
Section: Relevance For Brain-machine Interfacessupporting
confidence: 87%
“…We formalized it as a classification problem and chose the mean spike rate during the planning epoch of each trial and multiunit as our input signal (Taylor et al, 2002;Brown et al, 2004;Musallam et al, 2004;Hochberg et al, 2006;Achtman et al, 2007;Velliste et al, 2008).…”
Section: Real-time Decodingmentioning
confidence: 99%
“…In order to develop a classification strategy aimed at identifying separable neural states from real-time recordings, we chose to base our work on previous non-linear Bayesian Maximum Likelihood Estimation schemes [15,[21][22][23]. A non-linear decoding scheme was selected as prior studies have indicated that there is significant non-linear information present in the neural recordings [1,9,[23][24][25][26].…”
Section: Experimental Design and Methodsmentioning
confidence: 99%